Potential Impacts of Lead on Health: A Review of Environmental Exposure, Population at Risk, and Toxic Effects - Simatupang, Meithyra Melviana; Veronika, Erna; Irfandi, Ahmad; Azteria, Veza (Universitas Airlangga, 2024)
Introduction: Lead, a heavy metal, has been proven to influence the ecosystem negatively. The use of lead in processing or as raw materials increases Pb exposure to humans from various sources, including waste or consumed products. This study aims to determine the most recent information regarding lead contamination sourced from the environment, at-risk populations, and the health impacts of this heavy metal contamination. Results and Discussion: This systematic review used a database sourced from Google Scholar. The keywords searched were